Study of Palm Oil Shell Utilization as Metallurgical Coke with Variation of Bondcrete Additive - Hariyadi, Asful; Khoirunnisa Hidayat, Dinda; Purwanto, Moch. (Jurnal Teknik Kimia dan Lingkungan, 2024)
Coke, an essential ingredient in the steel and metallurgical industries, is typically derived from bituminous coal. However, in Indonesia, where bituminous coal is rare, coke production is dependent on coal imports due to the high moisture content of local coal. An alternative approach is to use biomass, such as palm oil processing waste, for "biomass coke" to produce a more environmentally friendly coke with lower greenhouse gas emissions. Palm kernel shell waste rich in lignocellulose proved suitable for this purpose due to its compressive strength and carbon content. Pyrolysis, a technique for creating porous micro-structured carbon from palm kernel shells, was used to produce this coke substitute, offering a more sustainable energy source with a lower carbon footprint than fossil fuels. Bio-coke exhibits low moisture content (5.84%) and ash content (13.20%) due to the moisture and ash reduction effects of bondcrete adhesive during combustion. It also demonstrates substantial compressive strength (14 mPa), a high calorific value (6795 cal/g), and a favorable pore structure with a large surface area, indicating a positive influence of bondcrete adhesive on coke properties without compromising energy potential.